Holographic dynamics as a way to solve the basic cosmological problems - Bolotin, Yu.L.; Lemets, O.A.; Yerokhin, D.A.; Zazunov, L.G. (Вопросы атомной науки и техники, 2012)
We review recent results on the cosmological models based on the holographic principle which were proposed to explain the most of the problems occurring in the Standard Cosmological Model. It is shown that these models naturally solve the cosmological constant problem and coincidence problem. Well-documented cosmic acceleration at the present time was analyzed in the light of holographic dark energy. In particular, we showed that in the model of the universe consisting of dark matter interacting with a scalar field on the agegraphic background can explain the transient acceleration. We also study the impact of ideas of the physics of entangled states on these cosmological models. Entanglement entropy of the universe gives holographic dark energy with the equation of state consistent with the current observation data. Рассмотрены космологические модели, основанные на голографическом принципе, позволяющие облегчить решение таких космологических проблем, как проблема космологической постоянной и проблема совпадений, а также объяснить ускоренное расширение Вселенной. В частности, мы показали, что модель Вселенной, состоящая из тёмной материи, взаимодействующая со скалярным полем, на фоне голографической тёмной энергии может объяснить переходное ускорение. В работе также рассмотрено влияние идей физики запутанных состояний на космологические модели. Розглянуто космологічні моделі, засновані на голографічному принципі, які можуть не тільки пояснити прискорене розширення Всесвіту, але й дають можливість вирішити проблему космологічної постійної та проблему збігів. Зокрема, ми показали, що модель Всесвіту, заповненого темною матерією, яка взаємодіє зі скалярним полем, на фоні голографічної темної енергії може пояснити перехідне прискорення. В роботі також розглянуто вплив ідей фізики заплутаних станів на космологічні моделі.